Number of People who Inject Drugs in Son La, Vietnam: Population Size Estimation Based on Official Records - Le Anh Tuan; Nguyen Thi Thanh Ha; Quan Dinh Nguyen; Giang Tong Le; Duong Cong Thanh; Meade Morgan; Abu S. Abdul-Quader (Springer, 2020)
Aims: Estimated population sizes of key populations are critical for resource allocation as well as for monitoring program performance to prevent HIV infection. In 2018, using official records we recruited and conducted a brief survey among People Who Use Drugs (PWUD) to estimate the population size of People Who Inject Drugs (PWID) in Son La Province, Vietnam. Methods: In Son La, the authorities develop and maintain a master list of individuals who are suspected of using drugs. The list is updated quarterly and is used to monitor the drug use situation in the province. The list, however, does not distinguish injecting from non-injecting drug users. Individual lists from six districts, 24 communes, and 96 hamlets were selected from among those from 12 districts, 204 communes, and 3335 hamlets in the whole province. After reviewing the lists with the hamlet health workers, based on the length of the lists, a minimum of 20% of the total or five drug users in any hamlet with fewer than 25 PWUD were randomly selected for a brief assessment. In addition to basic demographics, the assessment included any drug use in the last 3 months, injection drug use in the last 3 months, and the last time injected. Results: A total of 250 PWUD were interviewed by hamlet health workers. The total number of PWID across all 12 districts in Son La was estimated at 4475 [95% Confidence Interval (CI): 3379-5570] and the corresponding proportion of PWID among PWUD was 48.4% (95% CI: 36.6-60.4). Conclusion: The exercise provided an estimated number of PWID in Son La. For planning HIV prevention and care service needs among PWID, additional studies using different methods are needed to validate and improve the population size of PWID in the province of Son La.